FDI In India –An Effective Tool Of Continoues Growth: A Causality Analysis - Dr. Deepa Rawat, Dr.deepti, (International Journal of Scientific Research and Management (IJSRM), 2017)
India’s economic policy reforms, adopted at the backdrop of historical economic crises of 1990-91 and some notable changes in global economic set up, have changed the whole structure of Indian economy since 1991. Among other things, the reforms have evolved in opening the economy, making it more competitive, getting the government out of the huge mode of regulation, empowering the states to take more responsibility for economic management and creating a kind of competition among the states for foreign investors